A Review on the Relationship between Islam and Environmental Ethics With Emphasis on the View of Ayatullah Jawadi Amuli - Muhammad Taqi Islami (حکمت اسرا)
The most challenging problem in environmental ethics debates is the threatening environmental crisis which has been emerged due to the development in human material life. Those who are concerned together with researchers in this field have discussed on how to settle or manage the risk. The most important of these discussions include review on environmental ethical issues, understanding the correct moral relationship between human beings and natural organisms, finding the causes of environmental problems and difficulties, and criticism of manly western traditional morality in confrontation with the environment. In this article we try to enlighten these discussions and also draw the outlines of Islamic approach regarding the view of Hazrat Ayatullah Jawadi Amuli (may God protect him).